2019
DOI: 10.1253/circrep.cr-19-0070
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Canagliflozin, Dapagliflozin and Empagliflozin Added to Heart Failure Treatment in Decompensated Heart Failure Patients With Type 2 Diabetes Mellitus

Abstract: beneficial effect as a class effect on HF condition. 13,14 It remains unclear, however, whether the 3 SGLT2i are similarly effective for HF itself in patients with T2DM. As a preliminary step in the observation of the long-term effectiveness of SGLT2i, it is necessary to confirm the efficacy and safety in the short term. Therefore, the goal of this study was to compare the short-term efficacy and safety of the 3 SGLT2i, canagliflozin, dapagliflozin and empagliflozin in acute decompensated HF patients with T2DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 28 publications
(21 reference statements)
1
17
0
2
Order By: Relevance
“…Recent studies have reported that inhibition of SGLT1 receptors in the heart may decrease hyperglycemia-induced generation of reactive oxygen species, leading to potential prevention of heart failure [ 53 , 54 ]. In addition, compared to empagliflozin, dapagliflozin did not increase plasma aldosterone and noradrenaline levels, which may also prove beneficial for the prevention of hHF [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that inhibition of SGLT1 receptors in the heart may decrease hyperglycemia-induced generation of reactive oxygen species, leading to potential prevention of heart failure [ 53 , 54 ]. In addition, compared to empagliflozin, dapagliflozin did not increase plasma aldosterone and noradrenaline levels, which may also prove beneficial for the prevention of hHF [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall study design was detailed previously. 14) In brief, the present study was a single-center, non-randomized, open-labeled prospective registry study investigating the short-term efficacy and safety of SGLT2i (canagliflozin, dapagliflozin, and empagliflozin) in diabetic patients with acute decompensated HF. Eligible patients satisfied the enrollment criteria; aged !20 years and T2DM, which was defined as satisfying HbA1c !6.5% or In order to investigate the relationship between the effectiveness of SGLT2i and glycemic control, we stratified the patient cohort using baseline HbA1c (Group H: HbA1c !6.9%; Group L: HbA1c < 6.9%).…”
Section: Methodsmentioning
confidence: 99%
“…A detailed assessment of this early response to SGLT2i, instead of a chronic response, would be a key to further clarify the clinical impact of SGLT2i therapy. 14) In this study, we investigated the detailed early response to SGLT2i therapy in patients with acute decompensated HF who were stratified by the degree of HbA1c.…”
mentioning
confidence: 99%
“…[17][18][19] We previously reported that short-term SGLT2i therapy could successfully reduce the BNP level in HF patients. 16) The decrease in BNP level at an early stage of SGLT2i administration is presumed to reflect the acute diuretic effect. However, many previous studies, including ours, reported that the acute diuretic effect by SGLT2i is transient and unsustainable.…”
Section: Sglt2i and Bnpmentioning
confidence: 99%
“…Our team previously reported that short-term SGLT2i therapy corrected volume overload and ameliorated symptomatic pulmonary congestion in patients with ADHF and T2DM. 16) In this study, we investigated the impact of long-term SGLT2i therapy in patients with ADHF and T2 DM.…”
mentioning
confidence: 99%